Multidisciplinary Oral Rehabilitation of a Kennedy Class I Partially Edentulous Patient Using Corticobasal Implants with Immediate Functional Loading: A Case Report - Vaid, Rahul; Singh, Guljot; Ajmera, Pragya; Parkash, Jyoti; Chikhalikar, Shravani; Maurya, Ashiwini (Journal of Neonatal Surgery, 2025)
N\A